Growth response of Moringa oleifera Lam. as affected by various amounts of compost under greenhouse conditions - Laba, C.H.; Ngakou, A.; Yemefack, Martin; Mbailao, M. (Elsevier, 2017)
The study was carried out to assess the effect of domestic animal composts on growth performance of potted moringa. The study was conducted in the greenhouse for 55 days. Various quantities of composts (100–300 g) added to 800 g of soil were applied. A Randomized Complete Block Design (RCBD) with 14 treatments (each of which was replicated 12 times) was used, giving a total of 168 experimental units. Plant height, stem diameter, leave length and number of leaves were assessed for each treatment. Results indicate that cow dung compost (100 g, 200 g and 300 g) significantly increased the stem diameter of moringa by respectively 33.09%, 33.09%, and 29.93 as compared to that of the control 55 days after in the greenhouse. An increase in the number of leaves by 48.54% due to application of 100 g cow manure compost was observed after 40 days compared to the control. There were significant differences between treatments effects (p < .05) on all the parameters. Organic amendments in general and cow dung compost in particular could constitute the best fertilizer to improve growth moringa in pots.